Germplasm rescue and rebuilding local seed systems in red zone areas - Joshi, Bal Krishna; Gauchan, Devendra; Sapkota, Shreejana; Poudyal, Kritesh; Ghimire, Krishna Hari; Dongol, Durga Man Singh (Journal of Agriculture and Natural Resources, 2020)
Native agrobiodiversity become endangered and even lost due to natural disasters in red zone area such as earthquake that hit Nepal on April and May 2015. Endangered agricultural genetic resources should be rescued and revival of disrupted local seed system was essential for sustainable and productive agriculture in earthquake affected areas. The objectives of this paper are to document methods employed to rescue germplasm and rebuild local seed systems in earthquake affected areas to restore lost crop diversity and strengthen local seed systems. Among 14 severely hit districts by April 2015 earthquake in Nepal, 10 districts were selected for germplasm rescue and rebuilding local seed system. We surveyed households and sensitized relevant stakeholders. Earthquake affected areas were declared as red zones and status of crop landraces were assessed through survey, five cell analysis and focus group discussion. Three germplasm rescue techniques, namely direct rescue, diversity fair and indirect rescue were applied. Local seed systems were rebuilt through diversity fair, diversity block, seed exchange, repatriation and diversity kits. Collected accessions were characterized, multiplied and conserved in National Genebank and community seed banks. About 5-10% of total local crop diversity (based on the landraces) were lost due to earthquake in these districts. A total of 921 accessions of 61 crops along with 284 rare and endangered crop landraces were collected and rescued from 35 VDCs of 10 severely earthquake affected districts. Climate analogue sites and climate smart germplasm were identified for some of earthquake affected areas, and five landraces of four crops were repatriated. Participatory seed exchange, diversity fairs and 200 diversity kits (containing 3 to 5 varieties) were employed to revive the local seed systems. Farmers’ preferred landraces were conserved in Community Seed Bank in Lamjung and Dolakha and all collections were conserved in Naional Genebank, Khumaltar, Nepal. The study concludes that multiple approaches and tools are necessary for germplasm rescue and rebuilding local seed systems from red zone area